Revealed preferences for voluntary climate change mitigation when the purely individual perspective is relaxed: evidence from a framed field experiment - Löschel, Andreas; Sturm, Bodo; Uehleke, Reinhard (Journal of behavioral and experimental economics, 2017)
We investigate the demand for voluntary climate change mitigation when the purely individual perspective of existing revealed preference studies is relaxed. This is achieved in two treatments; first, we determine the information subjects receive about the demand revealed by other subjects in a similar decision making situation, second, collective action is implemented whereby all subjects are required to purchase the group's median quantity at a given price. Participants in the experiment were offered the opportunity to contribute to voluntary climate change mitigation by purchasing European Union Allowances. Purchased allowances were withdrawn from the European Emissions Trading Scheme. In our experiment, information about other subjects’ behavior has no effect on the demand for voluntary climate change mitigation. Under collective action, however, WTP, aggregate demand and the probability of purchasing allowances are higher compared to an individual contribution mechanism. Thus collective action curtails free riding, although it has no traceable effect on the provision level of the public good outside the experiment.
Gesehen am 10.07.2017